Responsible Innovation in the Development of Local Food Products by the Desa Prima Group in Sambirejo Gunungkidul - Diah Fitria Widhiningsih; Syarifa Nurul Auliya (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2023)
The number of competitors in the similar processed food business makes the business actors retain consumers and expand the sales scale. They should create new products through responsible innovation concept so that the product is carried out in a sustainable manner for social, economic, and environmental benefits. Therefore, this study aimed at: (1) analysing the preference of Desa Prima in adopting the food innovation and (2) analysing behaviour in the responsible innovation development. This was a mixed method research conducted in the Sambirejo, Ngawen, Gunungkidul and it employed six actors of Desa Prima. Primary data was collected through observation, in-depth interviews, and questionnaires. The data were analysed descriptively and the Cochran test was carried out to find out the preference in behaviour. The results showed that there was no difference in the frequency of planning activities, especially for consulting with families, considering pros and cons, and making product samples beforehand, although not all managers checked the taste quality. However, Desa Prima had not maximized the management of recipes and other activities in the form of SOPs. Regarding environmental sustainability, the processing of organic waste had not been maximized even though they showed the motivation to implement a zero-waste system.